Perkawinan Beda Agama Itu Boleh (?) - Susilo Surahman (Jurnal Multidisiplin Madani, 2022)
Marriage of different religions is one of the social phenomena of society that has the potential to have impact implications in the future. One of them is the conflict between marriage as a human right and the regulation of marriage that emphasizes validity based on religious beliefs. This study aims to explain marriages of different religions from various perspectives. This research is qualitative research with a normative approach. The results showed that the opinion that marriages of different religions are allowed are based on Article 57 of Law 1/1974, where there is a marriage clause that is subject to different laws. This allows for marriages of different nationalities and different religions. In addition, Law 1/1974 is considered to have a legal vacuum, which can be done the application of Regeling op de Gemengde Huwelijk (GHR). Another basis for the permissibility of marriage of different religions is the Civil Code. While opinions that say marriage of different religions are not allowed are based on Law 1/1974, FATWA MUI, and KHI. Law 1/1974 and Human Rights have two (two) different perspectives, between allowing and prohibiting marriage of different religions.